Development of Environmental Management Strategies for Slums in Southwest Aceh Regency - Husna, Cut Zulfa; Pravitasari, Andrea Emma; Putra, Andi Syah; Latifa, Nisa (Universitas Diponegoro, 2025)
Slums represent a complex issue found in various regions, including Southwest Aceh Regency, caused by poor management and inadequate settlement planning. This study analyzes the spatial patterns of slum areas in Southwest Aceh Regency and proposes management strategies. The research utilizes Moran's Index analysis and LISA to identify spatial clustering patterns of slum areas, complemented by SWOT analysis to determine suitable environmental management strategies. Moran's Index analysis of slums in Southwest Aceh Regency for 2014 and 2020 reveals a positive spatial autocorrelation with clustered pattern, but less concentration in 2020. LISA analysis shows the spatial distribution of slum areas in 2014 showed high-high (HH) clusters concentrated along coastal and mid-district regions, while in 2020, clustering shifted and became concentrated in the regency capital. Overall, the distribution of slums in 2020 appears more dispersed. The primary environmental management strategy recommended for slum upgrading in Southwest Aceh Regency a Defensive Strategy. This involves strengthening stakeholder collaboration to improve sanitation infrastructure, thereby mitigating disaster risks such as flooding; reorganizing residential areas to accommodate urbanization while attracting developers; and educating the community to enhance compliance with environmental regulations. Additionally, maintaining financing programs despite potential budget reductions is critical to ensuring sustainable living conditions.